A comparative study of effects of different freezing methods on sperm quality, DNA integrity and membrane protein of cryopreserved boar semen - BAISHYA, S K; BISWAS, R K; KADIRVEL, G; DEKA, B C; KUMAR, SURESH (The Indian Journal of Animal Sciences, 2018)
The present study determined the effects of conventional, and controlled freezing method adopting three freezing rates, viz. 20°C, 40°C and 60°C/min on quality of sperm (motility, viability and plasma membrane integrity), DNA integrity and plasma membrane protein profile of cryopreserved boar semen. Sixty sperm-rich fractions of ejaculates from six boars were utilized for freezing of semen with different freezing methods in lactose-egg yolk glycerol extender. Semen samples were evaluated for sperm motility, viability (Propidium Iodide assay), functional integrity of plasma membrane (HOST), DNA integrity (Acridine Orange stain) and plasma membrane protein profile (SDSPAGE) after equilibration and after freezing. The results revealed that the post thaw sperm motility, sperm viability, and plasma membrane integrity (HOST-reacted) were significantly higher in all the three controlled freezing methods (20°C, 40°C and 60°C/min) as compared to that in conventional method. In addition, the number of sperm plasma membrane protein loss was less in controlled freezing methods as compared to that in conventional freezing. However, the post thaw sperm DNA integrity did not influence by difference in freezing methods. No significant difference on the post thaw sperm characteristics was recorded among the three controlled freezing rates. All the sperm parameters assessed declined significantly after freezing as compared to that after equilibration irrespective of freezing method employed. In conclusion, controlled freezing methods conferred better post thaw sperm quality as compared to conventional method, and thus the freezing rates of either 20, 40 or 60°C/min could provide better freezability of boar semen.